Sex, Race, and Job Satisfaction among Highly Educated Workers - Joni Hersch; Jean Xiao (Institute for the Study of Labor (IZA), 2015)
There has been a considerable amount of work focusing on job satisfaction and sex, generally finding that women are more satisfied than men despite having objectively worse job conditions. But there is little evidence on whether job satisfaction differs by race or ethnicity. We use data from the 2010 National Survey of College Graduates to examine the relation between job satisfaction and race and ethnicity among Asian, black, Hispanic/Latino, and white workers. Overall job satisfaction does not differ by sex among college graduates. Relative to white workers of the same sex, Asian and black workers are far less satisfied. The lower satisfaction of Asian and black workers relative to white workers is not explained by immigrant status, job match, or other individual or job characteristics.
Keywords: J15; J16; J28; J71; 330; job satisfaction; gender; race and ethnicity; immigrants; college graduates; discrimination